Train speed profile optimization with on-board energy storage devices: A dynamic programming based approach. (December 2018) - Huang, Yeran; Yang, Lixing; Tang, Tao; Gao, Ziyou; Cao, Fang; Li, Keping
Highlights: On-board energy storage device is considered in speed profile optimization to reduce energy consumption. Increased train mass is taken into account with installation of onboard energy storage device. Relevant running time is adjusted to maximize regenerative energy and guarantee transit capacity. We propose a dynamic programming based heuristic method to find the approximate optimal speed profiles. Abstract: Aimed to increase usage of regenerative energy and stabilize voltage variation of traction supply grid, an energy-saving model with on-board energy storage devices is proposed by jointly optimizing the running time and recommended speed profile of trains over the whole urban rail transit line. Regenerative energy, generated by the braking train, is considered to store into its individual on-board energy storage devices and provided for the follow-up traction operations. Some parameters, including the comfort criterion and increased train mass due to the installation of energy storage devices, are all taken into account in the energy consumption calculation. In the optimization process, the total running time is only required to be adjusted in a predetermined range to guarantee transportation capacity and meet passenger travel demands. A dynamic programming based heuristic is designed with operational experiences and a series of numerical experiments are implemented to demonstrate the effectiveness, corresponding to Beijing metro Yizhuang line.